Medium der konkurrierenden Herrschaftsrepräsentation? Hofoper und Hofmusik im Spiegel der Wiener Gesandtschaftsberichte aus Berlin (1740-1780) - Henzel, Christoph (Die Musikforschung, 2019)
It is a truth universally acknowledged that opera seria was designed as a power-enhancing spectacle to impress not only local publics but also foreign courts, particularly the major European power players. Modern scholarship considers official envoys as the main agents of transmitting information about performances, titles, storylines and the meaning of operas. However, this common perception can be disproved by evaluating the reports of the Austrian embassy in Berlin between 1740 and 1780, the critical years of political rivalry between Austria and Prussia. Music and opera are rarely mentioned in the coverage of court and political news; a targeted interest in their aesthetic value or potential political interpretation did not exist. These findings challenge common perceptions of serious opera as a means of princely representation between the courts of the ancien regime.